A survey of knowledge, attitude and practice of biomedical waste management among 150 nursing staff working in All Indian Institute of Medical Sciences, Jodhpur - Chhabra, Vivek; Meena, Durga Shankar; Bohra, Gopal Krishana; Midha, Naresh; Maheshwari, Bharat; Rohilla, Amit (International Journal Of Community Medicine And Public Health, 2019)
Background: India as a developing country is facing a lot of health care problems, with the increase in health care facilities, there is a growing concern of hazards of biomedical waste. Since the nursing staff is at the centre of biomedical waste handling, their knowledge of adequate disposal of biomedical waste is of utmost importance. So, we conducted a study regarding knowledge, attitude and practice of nursing staff working in a premier institute of western Rajasthan with respect to biomedical waste and its management. Methods: This was a hospital-based descriptive, observational study conducted in our institute in the month of October and November of 2018. Written consent was taken and pre-defined questionnaire was prepared based on a review of literature on the subject. Scrutiny was done for the data for any logical inconsistencies, skip patterns and missing values. Coding of the data was done and entered into a Microsoft Excel. Descriptive and inferential statistics were applied for data analysis. Results: 150 participants took part in the questionnaire based study. The study showed that majority of participants have adequate knowledge, attitude and practice toward biomedical waste management but still, there were gaps in the knowledge and practice in essentially quite a lot of participants which should not be there. Conclusions: There is a need for strict implementation of biomedical rules at all the tiers of healthcare. There should be regular orientation programs for nursing staff and other health personnel working in the institutes.